Archaeology From Space : how the future shapes our past - Parcak, Sarah H. (New York: Henry Holt and Company, 2019)
"A down-and-out so-and-so gets more than she bargained for when new technologies developed for use in space allow an anthropologist a new perspective on earth's ancient histories and new ways of coping with those"--
Time capsule -- Space archaeology -- The promise of space archaeology -- A risky business -- Digging in the wrong place -- A grand tour -- Empires fall -- A capital discovery -- The future of the past -- The challenge -- Stolen heritage -- Space archaeology for everyone -- Acknowledgments.
Includes bibliographical references and index.
Keywords: Archaeology -- Remote sensing; Artificial satellites in remote sensing; Aerial photography in archaeology; Space photography